The Influence of The Problem Based Learning Model Assisted with Online-Based Practicum Media on Learning Outcomes in Excretion System Subject Matters - Ningsih, Armita; Kahiruna, Khairuna; Jayanti, Ummi Nur Afni Dwi (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This research aims to: 1) determine the differences in student learning outcomes with the conventional model and the PBL model on the excretion system material, 2) determine the differences in student learning outcomes with the conventional model and the PBL model assisted by online-based practicum media on the excretion system material, and 3) knowing that there is a significant influence from the application of the PBL model assisted by online-based practicum media on student learning outcomes in the excretory system material. This research method uses a quantitative approach, using a quasi-experimental design research type, with a non-equivalent control group design research design. The sampling technique was carried out using saturated sampling, and the data collection process used test instruments in the form of pretest and posttest questions. The results of this research are 1) There are differences in student learning outcomes between the conventional model and the PBL model, indicated by the average value of the posttest data of 67.39 < 70.86. 2) There are differences in student learning outcomes between the conventional model and the PBL model assisted by online-based practicum media, shown by the average value of posttest data of 67.39 < 79.00. 3) There is a significant influence from the application of the Problem-Based Learning model assisted by online-based practicum media on student learning outcomes in the excretion system material, shown by the sig value. 0.00 < 0.05. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28633